Antituberculosis Drugs Induced Hepatitis - Patel, Niyati; Gandhi, Riya; Dave, Padmja; Mistry, Mahek (Journal of Pharmacy Practice and Community Medicine)
Background: Tuberculosis, also called as TB, is a highly contagious bacterial infection and can be found nearly anywhere in the body, but lungs are the most common site of infection. Among the first line combination therapy drugs (INH, RMP, PZA, EMB), INH, RMP, and PZA are hepatotoxic as they are potentially metabolized mainly by the liver. Case: This is a case report of 18 years old male patient who was diagnosed with hepatitis after administration of anti TB drugs. He was admitted to the hospital for dry cough, loss of appetite, weight loss 3-5kg before 1 month. Laboratory investigations and other reports confirmed hepatitis. In this case, patient was receiving the anti TB drugs since 1 month and then later developed hepatitis which is a severe adverse drug reaction. Conclusion: Although hepatotoxicity is severe side effects of antituberculosis drugs. Following standard treatment and care of the patient we archive favourable outcome.
Keywords: Anti tubercular drugs; Hepatitis; SGOT; SGPT; Adverse Drug Reaction.